(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The nascent debate on corporate governance in India has tended to drawheavily on the large Anglo-American literature on the subject. This paperargues however that the corporate governance problems in India are verydifferent. The governance issue in the US or the UK is essentially that ofdisciplining the management who have ceased to be effectively accountable tothe owners. The problem in the Indian corporate sector (be it the publicsector, the multinationals or the Indian private sector) is that ofdisciplining the dominant shareholder and protecting the minority shareholders.Clearly, the problem of corporate governance abuses by the dominant shareholdercan be solved only by forces outside the company itself. The paper discussesthe role of two such forces - the regulator and the capital market. Good governance means that processes and institutions produce resultsthat meet the needs of society while making the best use of resources at theirdisposal. Good corporate governance (GCG) is a mandatory requirement in today‘scorporate world by every stakeholder groups. It is useful at this point to take a closer look at corporategovernance abuses by dominant shareholders in India. The problem of thedominant shareholder arises in three large categories of Indian companies.First are the public sector units (PSUs) where the government is the dominant(in fact, majority) shareholder and the general public holds a minority stake(often as little as 20%). Second are the multi-national companies (MNCs) wherethe foreign parent is the dominant (in most cases, majority) shareholder. Thirdare the Indian business groups where the promoters (together with their friendsand relatives) are the dominant shareholders with large minority stakes,government owned financial institutions hold a comparable stake, and thebalance is held by the general public.